2023
DOI: 10.21203/rs.3.rs-2397523/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineering Climate-Resilient Rice Using a Nanobiostimulant-based “Stress Training” Strategy

Abstract: Under a changing climate, cultivating climate-resilient crops will be critical to maintaining food security. Here, we propose the application of ROS-generating nanoparticles as nanobiostimulants to trigger stress/immune responses, and subsequently increase the stress resilience of plants. We established three regimens of AgNPs-based “stress training”: seed priming (SP), leaf priming (LP), and combined seed- and leaf- priming (SLP). Trained rice seedlings were then exposed to either rice blast fungus (M. oryzae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Reactive oxygen species (ROS) production is an indicator of cytotoxicity, which has been reported being involved in nanoplastics' toxicity. 40,41 After the 72 h exposure, the superoxide dismutase (SOD) content was higher in all PS-NP treatments than that of the control (Figure 4b and Figure S13, P < 0.001), and the GSH content was also decreased upon the PS-100 (0.1 and 1.0 mg/L, P < 0.001) and PS-500 (1.0 mg/L, P < 0.001) treatments in comparison with that of the control (Figure 4b and Figure S13), suggesting that all PS-NPs induced oxidative stress in nematodes. Further study suggested that the exposure to PS-NPs triggered growth inhibition and increased the mortality of nematodes (Figure 4b and Figure S13).…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species (ROS) production is an indicator of cytotoxicity, which has been reported being involved in nanoplastics' toxicity. 40,41 After the 72 h exposure, the superoxide dismutase (SOD) content was higher in all PS-NP treatments than that of the control (Figure 4b and Figure S13, P < 0.001), and the GSH content was also decreased upon the PS-100 (0.1 and 1.0 mg/L, P < 0.001) and PS-500 (1.0 mg/L, P < 0.001) treatments in comparison with that of the control (Figure 4b and Figure S13), suggesting that all PS-NPs induced oxidative stress in nematodes. Further study suggested that the exposure to PS-NPs triggered growth inhibition and increased the mortality of nematodes (Figure 4b and Figure S13).…”
Section: Resultsmentioning
confidence: 99%
“…Ag + -Priming Promotes ROS Production in Rice Seeds. According to Zhao et al, 15,16 we hypothesized that reactive oxygen species (ROS) play an important role in triggering defense responses against Cu in rice. The EPR spectrum revealed more obvious signals of • OH in Ag +priming seeds (Figure S7a).…”
Section: Seed Ag + -Priming Enhances Root Cell Viability and Root Mor...mentioning
confidence: 99%
“…13−15 Seed priming acts as a "vaccine" to produce ROS as a signaling molecule to reprogram the metabolism and transcriptome of a plant, thereby enhancing plant resistance to biotic and abiotic stresses during growth. 15,16 Seed priming can effectively reduce the uptake of heavy metals in plants by modulating the expression of heavy metal transporter proteins and enhancing antioxidant enzyme activities. For example, ZnO-NP seed priming improved the growth of rice and reduced Cd uptake by increasing the activity of antioxidant enzymes and altering alanine, aspartic acid, and glutamic acid metabolism, while SiNPs improved the growth of wheat and reduced the Cd content by increasing the activity of antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation